VD_FINDINFO Arrêt / 2016 / 327 vom 12. April 2016 - VD Tribunal cantonal (2016)
AUTORITÉ PARENTALE CONJOINTE, RELATIONS PERSONNELLES, INTERNATIONAL, MESURE PROVISIONNELLE | 273 CC, 301a CC, 445 CC, 450 CC